The Difference in the Learning Achevement in Civic Education by Using Blended Learning Models - Susilawati, Evi; ., Atmawarni; Andriany, Liesna (International Journal of Engineering and Technology, 2018)
The aim of this research wasto see the differences of the usage of model blended learning towards the learning achievement in civic education in students of the Faculty of education science education North Sumatera Islamic University.The sample of this research was conducted on a Mathematical Education Study Program numbered 20 people and Biology Education Study Program numbered 18 people carried out on in the teachings of the 2017/2018. Hypothesis testing is done using analysis of variance (Anava) one way at 0.05 significance level by using the SPSS program 24.0 for Windows. Test the hypothesis on this research used independent T test. Based on the results of the Testing is significant value of 0.032.Next, the value of significant 0.032 < 0.05H0 is rejected and then accepted the H1 so that Ir can be concluded that there is a difference in learning achievement in Civic Education on student of Mathematic Education Study Program and Biology Education Study Program.Â Â